Complete traumatic laceration of the superior mesenteric vein after a blunt abdominal injury in a pediatric patient - Lešková, Jana; Leško, Michal; Štichhauer, Radek; Guňka, Igor (Acta chirurgica Belgica, 2025)
BACKGROUND: Isolated injury to the superior mesenteric vein (SMV) caused by blunt abdominal trauma is rare but often lethal, especially in pediatric patients. Due to the low incidence of SMV injuries, there are no universal guidelines for its diagnosis and treatment. The diagnosis is made using either computed tomography (CT) or intraoperative exploration. Primary vascular repair is recommended. CASE REPORT: A 10-year-old girl was transferred to a trauma center after a high-energy motor vehicle collision. Under the diagnosis of acute abdomen with hemoperitoneum, the patient underwent urgent laparotomy, 34 min after admission to the hospital. A complete laceration of the SMV trunk was observed. Definitive vascular repair of the transected SMV was performed. An interposition graft from the internal jugular vein was used with a good postoperative course. CONCLUSION: This case report demonstrates that definitive vascular repair of the SMV reduces the risk of intestinal ischemia and should be performed in cases where ligation presents a real threat to small bowel viability. In cases of severe SMV injury, the internal jugular vein is a high-quality and easily accessible graft.
Keywords: počítačová rentgenová tomografie; Vascular Surgical Procedures; Mesenteric Veins; Humans; dítě; Wounds, Nonpenetrating; Child; Female; tupá poranění; lidé; Abdominal Injuries; Vascular System Injuries; poranění břicha; lacerace; dopravní nehody; laparotomie; Laparotomy; ženské pohlaví; Accidents, Traffic; výkony cévní chirurgie; Tomography, X-Ray Computed; Lacerations; poranění cév; vena mesenterica